2019
DOI: 10.1093/europace/euy303
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of thoracoscopic vs. catheter ablation for atrial fibrillation

Abstract: Aims Video-assisted thoracoscopic surgery (VATS) ablation has been advocated as a treatment option for non-paroxysmal atrial fibrillation (AF) in recent guidelines. Real-life data on its safety and efficacy during a centre’s early experience are sparse. Methods and results Thirty patients (28 persistent/longstanding persistent AF) underwent standalone VATS ablation for AF by an experienced thoracoscopic surgeon, with the first 20 cases proctored by external surgeons. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…However, in the recent studies, thoracoscopic ablation was not superior to RF catheter ablation in persistent AF. 10 , 12 In the present study, we also showed that the efficacy of two different rhythm control strategies did not differ even at long-term follow-up. Considering that PV gaps were more frequent in the RF catheter ablation group than in the thoracoscopic ablation group at the redo procedure, direct PV antral clamping from the epicardial side might be more effective in creating durable transmural lesions than endocardial point-by-point ablation.…”
Section: Discussionsupporting
confidence: 73%
“…However, in the recent studies, thoracoscopic ablation was not superior to RF catheter ablation in persistent AF. 10 , 12 In the present study, we also showed that the efficacy of two different rhythm control strategies did not differ even at long-term follow-up. Considering that PV gaps were more frequent in the RF catheter ablation group than in the thoracoscopic ablation group at the redo procedure, direct PV antral clamping from the epicardial side might be more effective in creating durable transmural lesions than endocardial point-by-point ablation.…”
Section: Discussionsupporting
confidence: 73%